2009
DOI: 10.1021/ic900437x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermostructural Studies of a CuFe1−xCrxO2 Delafossite Solid Solution with 0 ≤ x ≤ 1

Abstract: In this work, different CuFe(1-x)Cr(x)O(2) compositions with 0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 38 publications
3
44
0
1
Order By: Relevance
“…[34,35] As the www.advelectronicmat.de (3 of 7) 1600341 wileyonlinelibrary.com ionic radius of Mg 2+ (0.720 Å) is larger than that of Cr 3+ (0.615 Å), our observations for the continuous but not linear increases in lattice parameter c up to x ≈ 0.025 provide clear evidence for the solubility of Mg on the octahedral delafossite site in our ALD-grown Cu(Cr 1−x Mg x )O 2 thin films, but the exact extent of solubility remains somewhat ambiguous. [47] In Figure 2 we first plot the room-temperature electrical resistivity (ρ) and Seebeck coefficient (S) values as a function of x for our Cu(Cr 1−x Mg x )O 2 films (upper figure), and then show the temperature dependence of ρ and S in the lower figure for the x = 0.035 film. First, the temperature dependence of resistivity shows a purely semiconducting behavior with dρ/dT < 0, and the positive Seebeck values confirm the p-type electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] As the www.advelectronicmat.de (3 of 7) 1600341 wileyonlinelibrary.com ionic radius of Mg 2+ (0.720 Å) is larger than that of Cr 3+ (0.615 Å), our observations for the continuous but not linear increases in lattice parameter c up to x ≈ 0.025 provide clear evidence for the solubility of Mg on the octahedral delafossite site in our ALD-grown Cu(Cr 1−x Mg x )O 2 thin films, but the exact extent of solubility remains somewhat ambiguous. [47] In Figure 2 we first plot the room-temperature electrical resistivity (ρ) and Seebeck coefficient (S) values as a function of x for our Cu(Cr 1−x Mg x )O 2 films (upper figure), and then show the temperature dependence of ρ and S in the lower figure for the x = 0.035 film. First, the temperature dependence of resistivity shows a purely semiconducting behavior with dρ/dT < 0, and the positive Seebeck values confirm the p-type electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…where r h is the hopping distance (i.e., the Cu-Cu distance a [16]) and N c is the number density of effective charge carrier. Using (8), N c can be evaluated at room temperature and compared to the number density of Cu sites in CuFe 1-x Cr x O 2 delafossite.…”
Section: And Ac Conductivitymentioning
confidence: 99%
“…CuCrO 2 delafossite is also a p-type semiconductor but with a lower intrinsic electrical conductivity (σ RT = 3.5 10 -5 S.cm -1 ) [9] due to the difficulties in intercalating oxygen into the stoichiometric delafossite structure [16]. However, the electrical conductivity can be also improved up to 220 S.cm -1 with appropriate M-site doping like in CuCr 0.95 Mg 0.05 O 2 thin film [8], by the same way than CuFeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of four-component delafossite compounds, there are reports which describe the growth and characterization of substitutional formations, for example CuFe 1-x Cr x O 2 [17], CuCr 1-x Ni x O 2 [18] and [19]. More specific to this work, the chemical synthesis and characterization of CuGa 1-x Fe x O 2 delafossite has been reported previously [20], where it was shown that the substitution of Ga for Fe within CuGaO 2 compounds led to a strong absorption edge measured at 1.5eV which was not observed in the host lattice material CuGaO 2 , This strong absorption was attributed to the activation of forbidden optical channels by crystal symmetry breaking within the host material rather than solely due to the hybridization of band-structures described by the empirical Vegard's law.…”
Section: Introductionmentioning
confidence: 99%